Efektivitas Asap Cair Kulit Sawit (Elaeis Guineensis Jacq) sebagai Antiseptik terhadap Mikroba - Sulistyawati, Annisa Lathifah; Dayanti, Nyimas; Iman, Moch Fajar Anugrah; Fadhila, Feldha; Maryana, Yayan; Rumidatul, Alfi (Jurnal Biomedika dan Kesehatan, 2023)
Background Bacteria and fungi that enter through the body get intermediaries from the condition of hands that are not washed clean. Alcohol-based antiseptics are usually used for quick and effective hand washing, but repeated use can cause irritation and dryness of the hands. Natural components can be processed to make non-alcoholic substitutes, such as liquid smoke from palm oil's outer shell (Elais guineensis Jacq). It is known that liquid smoke contains antibacterial phenolic chemicals. Methods This research design is true experimental by testing the effectiveness of palm oil outer shell liquid smoke as an antiseptic, which is carried out in vitro using inhibitory tests and in vivo using palm swabs of respondents by looking at the effects before and after use. In vitro results formed the largest inhibition zone size using grade 2 liquid smoke with a concentration of 75%, with an inhibition zone size of Staphylococcus aureus ATCC 25923 of 15.6 mm; Escherichia coli ATCC 25922 of 5.8 mm; Candida albicans ATCC 10231 of 3.3 mm; and Aspergillus flavus ATCC 9643 of 33.3 mm. Results In vivo, results obtained through the respondent's palm swab showed an average value of 89.84% decrease in bacterial colonies and a 77% decrease in fungal colonies after using liquid smoke antiseptic. The results of the organoleptic assessment showed that 92% of respondents liked the color, 75%  liked the smell, 75% felt that it did not cause dryness, and 92% felt that there were no side effects of use. Conclusions The liquid smoke of the outer shell of palm oil has the potential as an antiseptic.